Buried bumper syndrome: A complication of percutaneous endoscopic gastrostomy - Cyrany, Jiri (World J Gastroenterol, 2016)
Percutaneous endoscopic gastrostomy (PEG) is a widely used method of nutrition delivery for patients with long-term insufficiency of oral intake. The PEG complication rate varies from 0.4% to 22.5% of cases, with minor complications being three times more frequent. Buried bumper syndrome (BBS) is a severe complication of this method, in which the internal fixation device migrates alongside the tract of the stoma outside the stomach. Excessive compression of tissue between the external and internal fixation device of the gastrostomy tube is considered the main etiological factor leading to BBS. Incidence of BBS is estimated at around 1% (0.3%-2.4%). Inability to insert, loss of patency and leakage around the PEG tube are considered to be a typical symptomatic triad. Gastroscopy is indicated in all cases in which BBS is suspected. The depth of disc migration in relation to the lamina muscularis propria of the stomach is critical for further therapy and can be estimated by endoscopic or transabdominal ultrasound. BBS can be complicated by gastrointestinal bleeding, perforation, peritonitis, intra-abdominal and abdominal wall abscesses, or phlegmon, and these complications can lead to fatal outcomes. The most important preventive measure is adequate positioning of the external bolster. A conservative approach should be applied only in patients with high operative risk and dismal prognosis. Choice of the method of release is based on the type of the PEG set and depth of disc migration. A disc retained inside the stomach and completely covered by the overgrowing tissue can be released using some type of endoscopic dissection technique (needle knife, argon plasma coagulation, or papillotome through the cannula). Proper patient selection and dissection of the overgrowing tissue are the major determinants for successful endoscopic therapy. A disc localized out of the stomach (lamina muscularis propria) should be treated by a surgeon.